Monocrystal ternary positive electrode material as well as preparation process and application thereof
Through the three-stage program temperature-controlled calcining process and appropriate process parameter control, the problem of high lithium-nickel mixing in single-crystal ternary positive electrode materials is solved, and the discharge specific capacity of the material and the first-time Coulomb efficiency are improved.
Patent Information
- Application Number
- CN202311226568.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-21
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2043-09-21
Smart Images

Figure CN119695139A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of lithium-ion batteries, and in particular to a single-crystal ternary positive electrode material and a preparation process and application thereof. Background Art
[0002] With the development of society, fossil fuels are becoming increasingly depleted, and the development of new energy fields has received more and more attention. Rechargeable batteries are considered to be one of the most promising energy storage devices. Among many chemical power sources, lithium-ion batteries have attracted widespread attention due to their many advantages such as high energy density and long service life. As the positive electrode material of lithium-ion batteries, high-nickel ternary positive electrode materials with high specific capacity have become the focus of everyone's attention. The ternary positive electrode material with a layered structure is composed of alternating stacked lithium atomic layers and transition metal atomic layers. Since the radius of divalent nickel ions is close to that of lithium ions, lithium-nickel mixing is very likely to occur during material synthesis and electrochemical reactions, resulting in reduced structural stability, first coulomb efficiency and charge and discharge capacity of the material.
[0003] For traditional polycrystalline high-nickel ternary positive electrode materials, since their secondary balls are composed of a large number of smaller primary particles, a large number of grain boundaries are generated, which leads to side reactions with the electrolyte during the electrochemical reaction, and secondary ball cracking and other phenomena are prone to occur during the long cycle, resulting in rapid attenuation of battery performance. Therefore, single-crystal high-nickel ternary positive electrode materials have also become one of the hot areas of research. Single-crystal materials have the characteristics of large primary particles and smooth particle surfaces, and their structural stability and long-term cycle stability are significantly better than polycrystalline materials. CN112133904A discloses a lithium-ion battery high-nickel ternary positive electrode material and a preparation method thereof, the preparation method comprising the following steps: mixing a ternary precursor with lithium hydroxide, sintering once in an atmosphere furnace, adding a corrosion inhibitor after mixing the obtained product with water, washing, and mixing the obtained product with an oxide, and then sintering twice in an atmosphere furnace to obtain a positive electrode material. For single-crystal materials, because they require a higher calcination temperature than polycrystalline materials, serious lithium-nickel mixed row phenomena occur, which is not conducive to the performance of the material charge and discharge capacity and the first coulomb efficiency. Summary of the invention
[0004] In view of the problems that the single crystal ternary positive electrode material in the prior art has a high degree of lithium-nickel mixing, and a low charge-discharge capacity and first coulomb efficiency, the present invention provides a single crystal ternary positive electrode material and its preparation process and application. The single crystal ternary positive electrode material of the present invention is applied to lithium-ion batteries to significantly improve the discharge specific capacity and first coulomb efficiency.
[0005] The first aspect of the present invention provides a single crystal ternary positive electrode material, the chemical formula of which is Li x Ni y Co z Ma O b , where M is at least one of Mn and Al; 0.8 ≤ x < 1.2, 0.6 ≤ y ≤ 0.95, 0 < z ≤ 0.2, 0 < a ≤ 0.2. According to the valence state and content changes of different elements, the proportion of oxygen element conforms to the principle of electroneutrality; in the positive electrode material, the lithium-nickel mixing degree s is less than 4%, preferably less than 2%.
[0006] Furthermore, in the single-crystal ternary positive electrode material, the lithium-nickel mixing degree s satisfies: 0 < s < 4%, preferably 0 < s < 2%.
[0007] Furthermore, in the single-crystal ternary positive electrode material, 0.9 ≤ x < 1.1, 0.8 ≤ y ≤ 0.95, 0 < z ≤ 0.15, 0 < a ≤ 0.15; preferably, 0.9 ≤ x < 1.1, 0.8 ≤ y ≤ 0.95, 0 < z ≤ 0.05, 0 < a ≤ 0.15.
[0008] Furthermore, in the single-crystal ternary positive electrode material, the size of the primary particles is 2.0 - 5.0 μm, preferably 3.0 - 5.0 μm.
[0009] Furthermore, in the XRD pattern of the single-crystal ternary positive electrode material, the diffraction peak intensities I(003) and I(104) of the crystal plane (003) and the crystal plane (104) satisfy the following relationship: I(003) / I(104) is greater than 1.800, preferably greater than 1.900, and further preferably greater than 2.000.
[0010] Furthermore, in the XRD pattern of the single-crystal ternary positive electrode material, the diffraction peak intensities I(003) and I(104) of the crystal plane (003) and the crystal plane (104) satisfy the following relationship: 1.800 < I(003) / I(104) < 2.500, preferably 2.000 < I(003) / I(104) < 2.400.
[0011] Furthermore, in the single-crystal ternary positive electrode material, the c / a ratio in the lattice parameters is greater than 4.9350, preferably greater than 4.9365, and further preferably greater than 4.9380.
[0012] Furthermore, in the single-crystal ternary positive electrode material, the c / a ratio in the lattice parameters satisfies: 4.9350 < c / a < 4.9500, preferably 4.9380 < c / a < 4.9500.
[0013] The second aspect of the present invention provides a preparation process for a single-crystal ternary positive electrode material, including the following steps:
[0014] Mix the ternary positive electrode material precursor with a lithium source, calcine, and crush to obtain the single-crystal ternary positive electrode material.
[0015] Furthermore, the calcination adopts three-stage programmed temperature control calcination, wherein the temperature T1 of the first stage calcination is 400-600°C, the calcination time t1 is 4-7 hours, the temperature T2 of the second stage calcination is 800-1100°C, the calcination time t2 is 0.1-6 hours, and the temperature T3 of the third stage calcination is 600-900°C, and the calcination time t3 is 6-18 hours.
[0016] Furthermore, during the first stage calcination, the temperature is raised from room temperature (25-30°C) to T1 at a heating rate of 2-8°C / min. Preferably, the temperature T1 of the first stage calcination is 450-550°C, and the time t1 is 5-7 hours.
[0017] Furthermore, during the second stage calcination, the temperature is increased from T1 to T2 at a heating rate of 2-10°C / min. Preferably, the temperature T2 of the second stage calcination is 850-1000°C, and the time t2 is 0.5-4 hours.
[0018] Furthermore, during the third stage calcination, the temperature is reduced from T2 to T3 at a cooling rate of 2-10°C / min. Preferably, the temperature T3 of the third stage calcination is 700-800°C, and the time t3 is 9-15 hours.
[0019] Furthermore, in the three-stage programmed temperature-controlled calcination process, t2 is less than t1 and t3, and T2 is greater than T1 and T3. Preferably, the calcination temperature and time follow the rule of t3>t1>t2, and T2>T3>T1.
[0020] Furthermore, the lithium source is one or more of anhydrous lithium hydroxide, lithium hydroxide monohydrate, lithium carbonate, lithium phosphate, and lithium oxalate, preferably one or more of anhydrous lithium hydroxide and lithium hydroxide monohydrate.
[0021] Furthermore, the ternary cathode material precursor is a hydroxide precursor containing nickel-cobalt-manganese, nickel-cobalt-aluminum or nickel-cobalt-manganese-aluminum, and its chemical formula is Ni y Co z M a (OH)2, wherein M is at least one of Mn and Al; 0.6≤y≤0.95, 0<z≤0.2, 0<a≤0.2, and y+z+a=1; preferably, 0.8≤y≤0.95, 0<z≤0.15, 0<a≤0.15, and y+z+a=1; further preferably, 0.8≤y≤0.95, 0<z≤0.05, 0<a≤0.15, and y+z+a=1.
[0022] Further, the molar ratio of the lithium source to the ternary cathode material precursor in the mixture is 1:1 to 1.3:1, preferably 1.05:1 to 1.2:1.
[0023] Further, during the three-stage program calcination process, the calcination atmosphere is one of nitrogen, air or high-purity oxygen.
[0024] Further, the mixing is carried out by a conventional physical mixing method, such as grinding, so that the ternary cathode material precursor and the lithium source are in full contact.
[0025] Further, the crushing method is a method such as air flow crushing or ball milling crushing, and the crushing time is 2 to 10 hours.
[0026] Further, the chemical formula of the single-crystal ternary cathode material is Li x Ni y Co z M a O b , where M is at least one of Mn and Al; 0.8 ≤ x < 1.2, 0.6 ≤ y ≤ 0.95, 0 < z ≤ 0.2, 0 < a ≤ 0.2. According to the valence state and content changes of different elements, the proportion of oxygen element conforms to the principle of electroneutrality.
[0027] Further, in the single-crystal ternary cathode material, 0.9 ≤ x < 1.1, 0.8 ≤ y ≤ 0.95, 0 < z ≤ 0.15, 0 < a ≤ 0.15; preferably, 0.9 ≤ x < 1.1, 0.8 ≤ y ≤ 0.95, 0 < z ≤ 0.05, 0 < a ≤ 0.15.
[0028] Further, in the single-crystal ternary cathode material, the lithium-nickel mixing degree s is less than 4%, preferably less than 2%. Preferably, the lithium-nickel mixing degree s satisfies: 0 < s < 4%, preferably 0 < s < 2%.
[0029] Further, in the single-crystal ternary cathode material, the size of the primary particles is 2.0 - 5.0 μm, preferably 3.0 - 5.0 μm.
[0030] Further, in the XRD pattern of the single-crystal ternary cathode material, the diffraction peak intensities I(003) and I(104) of the crystal plane (003) and the crystal plane (104) satisfy the following relationship: I(003) / I(104) is greater than 1.800, preferably greater than 1.900, and further preferably greater than 2.000.
[0031] Further, in the XRD pattern of the single-crystalline ternary cathode material, the diffraction peak intensities I(003) and I(104) of crystal plane (003) and crystal plane (104) satisfy the following relationship: 1.800 < I(003) / I(104) < 2.500, preferably 2.000 < I(003) / I(104) < 2.400.
[0032] Further, in the single-crystalline ternary cathode material, the c / a ratio in the lattice parameters is greater than 4.9350, preferably greater than 4.9365, and more preferably greater than 4.9380.
[0033] Further, in the single-crystalline ternary cathode material, the c / a ratio in the lattice parameters satisfies: 4.9350 < c / a < 4.9500, preferably 4.9380 < c / a < 4.9500.
[0034] The third aspect of the present invention provides the application of the single-crystalline ternary cathode material as described above in a lithium-ion battery.
[0035] Further, the application includes: mixing, coating, and slicing the above-mentioned cathode material with a conductive agent and a binder for use as a battery cathode. The conductive agent and the binder can be various conductive agents and binders commonly used in the art. For example, the conductive agent can be selected from at least one of acetylene black, Ketjen black, graphite, carbon nanotubes, and graphene. The binder can be selected from at least one of polyvinylidene fluoride (PVDF), polyvinyl alcohol (PVA), and sodium carboxymethyl cellulose (CMC). The amounts of the conductive agent and the binder can also be conventional amounts in the art. For example, the mass ratio of the cathode material: conductive agent: binder is 0.8 - 0.96:0.1 - 0.02:0.1 - 0.02.
[0036] Further, the lithium-ion battery includes a cathode, an anode, a separator, and an electrolyte. There are no particular limitations on the anode, the separator, and the electrolyte, and those skilled in the art can make reasonable selections without creative efforts. For comparison purposes, in the embodiments of the present invention, metallic lithium is used as the anode, a 16-μm polyethylene microporous membrane of Jinhui Hi-Tech is used as the separator, and a 1 mol / L LiPF6 solution is used as the electrolyte, and the solvent is a mixed solvent of ethylene carbonate (EC) and diethyl carbonate (DEC) with a volume ratio of 3:7.
[0037] Further, the battery is assembled in an inert atmosphere glove box, and the moisture and oxygen content in the glove box are lower than 0.1 ppm. There is no particular limitation on the battery model. For comparison purposes, in the embodiments of the present invention, 2016-type coin cells are commonly used, and the electrochemical performance is tested on a Blue Power battery test system, and the electrochemical test temperature is 30°C.
[0038] The method of preparing lithium batteries using positive electrode materials is well known in the art and will not be described here.
[0039] Compared with the prior art, the present invention has the following beneficial effects:
[0040] (1) The present invention provides a novel single crystal ternary cathode material, which has a lower lithium-nickel mixing degree than general single crystal cathode materials. In the results obtained by XRD, the I(003) / I(104) peak intensity ratio is large, and the c / a ratio in the lattice parameters obtained by XRD refinement is large, indicating that the prepared ternary material has better crystallinity and stronger layered characteristics. When applied to lithium-ion batteries, the cathode material is endowed with higher discharge capacity and first coulomb efficiency.
[0041] (2) In the preparation process of the single crystal ternary positive electrode material of the present invention, the calcination adopts a three-stage programmed temperature rise method. By adjusting the parameters such as the calcination time and the roasting temperature in the temperature rise program, the melting of the lithium salt and the precursor hydroxide is promoted and a preliminary reaction occurs during the first stage of calcination. During the second stage of calcination, the highest T2 temperature is used to ensure the formation of the single crystal morphology of the positive electrode material, and the shortest t2 time is used to ensure the minimum energy consumption required for material preparation. In the third stage of calcination, the moderate T3 temperature and the longer t3 time are used to effectively reduce the degree of lithium-nickel mixing in the positive electrode material.
[0042] (3) The new single-crystal ternary positive electrode material prepared by the present invention is applied to button-type lithium batteries and exhibits higher discharge capacity and first coulombic efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 This is a SEM image of the single crystal ternary cathode material prepared in Example 1 of the present invention;
[0044] Figure 2 This is the XRD pattern of the single crystal ternary cathode material prepared in Example 1 of the present invention;
[0045] Figure 3 0.1C charge and discharge curve of the battery obtained in Example 1 of the present invention;
[0046] Figure 4 This is a cycle stability test curve of the battery obtained in Example 1 of the present invention. DETAILED DESCRIPTION
[0047] For ease of understanding of the present invention, the present invention enumerates embodiment as follows. But those skilled in the art should understand that the embodiment is only to help understand the present invention, should not be regarded as specific limitation of the present invention. The endpoints and any value of the range disclosed in this article are not limited to the precise range or value, and these ranges or values should be understood to include values close to these ranges or values.
[0048] All publications, patent applications, patents and other references mentioned in this specification are incorporated herein by reference. Unless otherwise defined, all technical and scientific terms used in this specification have the meanings commonly understood by those skilled in the art. In the event of a conflict, the definitions in this specification shall prevail.
[0049] In the context of this specification, any two or more aspects of the present invention may be arbitrarily combined, and the technical solutions thus formed belong to part of the original disclosure of this specification and also fall within the protection scope of the present invention.
[0050] Unless otherwise specified, all percentages, parts, ratios, etc. mentioned in this specification are based on weight, unless the weight basis does not conform to the common understanding of those skilled in the art.
[0051] In the present invention, the scanning electron microscope (SEM) images were obtained by using a Nova Nano 450 field emission scanning electron microscope.
[0052] In the present invention, the XRD pattern is measured by a D8ADVANCE X-ray diffractometer.
[0053] In the present invention, the obtained XRD spectrum is refined by using Topas software and Rietveld full spectrum fitting refinement method. When the reliability factor Rwp of the refined sample is less than or equal to 5%, the lithium-nickel mixing degree of the sample can be obtained.
[0054] In the present invention, the size of the primary particles is measured by using Nano measurer particle size analysis software on a scanning electron microscope image.
[0055] The present invention will be described in detail below through examples.
[0056] [Example 1]
[0057] (1) Preparation and evaluation of ternary cathode materials
[0058] Take 10g of high nickel ternary cathode material precursor Ni 0.83 Co 0.05 Mn 0.12 (OH)2, add 5g LiOH·H2O particles and mix and grind thoroughly;
[0059] The obtained homogeneous powder was subjected to high temperature treatment in a tube furnace and calcined in an oxygen atmosphere. The specific process was as follows: the temperature was increased from 25°C to 500°C at a heating rate of 5°C / min, maintained for 7 hours, then increased to 900°C at a heating rate of 10°C / min, maintained for 4 hours, then cooled to 700°C at a cooling rate of 5°C / min, maintained for 12 hours, and then naturally cooled to below 100°C and taken out;
[0060] The powder obtained after high-temperature calcination was ball-milled for 2 hours to obtain the ternary positive electrode material.
[0061] Figure 1 This is a SEM image of the ternary cathode material obtained in Example 1. As can be seen from the image, the obtained ternary cathode material mainly presents a single crystal morphology, and its primary particle size is 3.0-3.4 μm.
[0062] Figure 2 This is the XRD diagram of the ternary cathode material obtained in Example 1. It can be seen from the figure that the I(003) / I(104) peak intensity ratio of the obtained ternary cathode material is 2.139, and the c / a ratio of its lattice parameters obtained by refinement is 4.9387. The lithium-nickel mixing degree is 1.722%, which proves that the obtained high-nickel ternary cathode material has good crystallinity and its layered structure is well developed, and the lithium-nickel mixing degree is low.
[0063] (2) Electrochemical properties of cathode materials
[0064] The positive electrode material was mixed with conductive carbon and binder PVDF in a ratio of 0.9:0.05:0.05 in NMP and then coated on aluminum foil, dried, sliced, and assembled into a 2016-type button battery in a glove box.
[0065] Figure 3 The charge and discharge curve of the battery at a rate of 0.1C. As can be seen from the figure, the discharge capacity of the obtained battery at a rate of 0.1C is 181.1 mAh / g, and the first coulombic efficiency is 85.66%.
[0066] [Example 2]
[0067] (1) Preparation and evaluation of ternary cathode materials
[0068] Take 10g of high nickel ternary cathode material precursor Ni 0.83 Co 0.12 Mn 0.05 (OH)2, add 5g LiOH·H2O particles and mix and grind thoroughly;
[0069] The obtained homogeneous powder was subjected to high temperature treatment in a tube furnace and calcined in an oxygen atmosphere at a heating rate of 5°C / min from 25°C to 500°C, maintained for 7h, then heated to 900°C at a heating rate of 10°C / min, maintained for 4h, then cooled to 700°C at a cooling rate of 5°C / min, maintained for 12h, and then naturally cooled to below 100°C and taken out;
[0070] The powder obtained after high-temperature calcination was ball-milled for 2 hours to obtain the ternary positive electrode material.
[0071] SEM image of the ternary cathode material obtained in Example 2 Figure 1 Similarly, the primary particle size is 2.8-3.2 μm. XRD patterns are similar to Figure 2 The peak intensity ratio of I(003) / I(104) and the c / a ratio of the lattice parameters of the ternary cathode material were determined, and the specific results are shown in Table 1.
[0072] (2) Electrochemical properties of cathode materials
[0073] Lithium batteries were assembled according to the method described in Example 1 and the electrochemical performance was tested.
[0074] The electrochemical performance at a rate of 0.1C was measured, and the specific results are shown in Table 2.
[0075] [Example 3]
[0076] (1) Preparation and evaluation of ternary cathode materials
[0077] Take 10g of high nickel ternary cathode material precursor Ni 0.83 Co 0.05 Mn 0.12 (OH)2, add 5g LiOH·H2O particles and mix and grind thoroughly;
[0078] The obtained homogeneous powder was subjected to high temperature treatment in a tube furnace and calcined in an oxygen atmosphere at a heating rate of 5°C / min from 25°C to 550°C, maintained for 6 hours, then heated to 800°C at a heating rate of 10°C / min, maintained for 3 hours, then cooled to 600°C at a cooling rate of 5°C / min, maintained for 12 hours, and then naturally cooled to below 100°C and taken out;
[0079] The powder obtained after high-temperature calcination was ball-milled for 2 hours to obtain the ternary positive electrode material.
[0080] SEM image of the ternary cathode material obtained in Example 3 Figure 1 Similarly, the primary particle size is 2.0-2.2 μm. XRD patterns are similar to Figure 2The peak intensity ratio of I(003) / I(104) and the c / a ratio of the lattice parameters of the ternary cathode material were determined, and the specific results are shown in Table 1.
[0081] (2) Electrochemical properties of cathode materials
[0082] Lithium batteries were assembled according to the method described in Example 1 and the electrochemical performance was tested.
[0083] The electrochemical performance at a rate of 0.1C was measured, and the specific results are shown in Table 2.
[0084] [Example 4]
[0085] (1) Preparation and evaluation of ternary cathode materials
[0086] Take 10g of high nickel ternary cathode material precursor Ni 0.83 Co 0.12 Mn 0.05 (OH)2, add 5g LiOH·H2O particles and mix and grind thoroughly;
[0087] The obtained homogeneous powder was subjected to high temperature treatment in a tube furnace and calcined in an oxygen atmosphere at a heating rate of 5°C / min from 25°C to 500°C, maintained for 6 hours, then heated to 1050°C at a heating rate of 8°C / min, maintained for 5 hours, then cooled to 900°C at a cooling rate of 5°C / min, maintained for 15 hours, and then naturally cooled to below 100°C and taken out;
[0088] The powder obtained after high-temperature calcination is ball-milled for 8 hours to obtain the ternary positive electrode material.
[0089] SEM image of the ternary cathode material obtained in Example 4 Figure 1 Similarly, the primary particle size is 4.6-4.9 μm. XRD patterns are similar to Figure 2 The peak intensity ratio of I(003) / I(104) and the c / a ratio of the lattice parameters of the ternary cathode material were determined, and the specific results are shown in Table 1.
[0090] (2) Electrochemical properties of cathode materials
[0091] Lithium batteries were assembled according to the method described in Example 1 and the electrochemical performance was tested.
[0092] The electrochemical performance at a rate of 0.1C was measured, and the specific results are shown in Table 2.
[0093] [Example 5]
[0094] (1) Preparation and evaluation of ternary cathode materials
[0095] Take 10g of high nickel ternary cathode material precursor Ni0.83 Co 0.05 Mn 0.12 (OH)2, add 5.8g LiOH·H2O particles and mix and grind thoroughly;
[0096] The obtained homogeneous powder was subjected to high temperature treatment in a tube furnace and calcined in an oxygen atmosphere. The specific process was as follows: the temperature was increased from 25°C to 550°C at a heating rate of 5°C / min, maintained for 7 hours, then increased to 950°C at a heating rate of 8°C / min, maintained for 4 hours, then cooled to 700°C at a cooling rate of 5°C / min, maintained for 10 hours, and then naturally cooled to below 100°C and taken out;
[0097] The powder obtained after high-temperature calcination was ball-milled for 2 hours to obtain the ternary positive electrode material.
[0098] SEM image of the ternary cathode material obtained in Example 5 Figure 1 Similarly, the primary particle size is 3.5-3.7 μm. XRD patterns are similar to Figure 2 The peak intensity ratio of I(003) / I(104) and the c / a ratio of the lattice parameters of the ternary cathode material were determined, and the specific results are shown in Table 1.
[0099] (2) Electrochemical properties of cathode materials
[0100] Lithium batteries were assembled according to the method described in Example 1 and the electrochemical performance was tested.
[0101] The electrochemical performance at a rate of 0.1C was measured, and the specific results are shown in Table 2.
[0102] [Example 6]
[0103] (1) Preparation and evaluation of ternary cathode materials
[0104] Take 10g of high nickel ternary cathode material precursor Ni 0.83 Co 0.05 Mn 0.12 (OH)2, add 4.6g LiOH·H2O particles and mix and grind thoroughly;
[0105] The obtained homogeneous powder was subjected to high temperature treatment in a tube furnace and calcined in an oxygen atmosphere. The specific process was as follows: the temperature was increased from 25°C to 450°C at a heating rate of 5°C / min, maintained for 7 hours, then increased to 850°C at a heating rate of 10°C / min, maintained for 4 hours, then cooled to 700°C at a cooling rate of 5°C / min, maintained for 15 hours, and then naturally cooled to below 100°C and taken out;
[0106] The powder obtained after high-temperature calcination was ball-milled for 2 hours to obtain the ternary positive electrode material.
[0107] SEM image of the ternary cathode material obtained in Example 6 Figure 1 Similarly, the primary particle size is 3.2-3.6 μm. XRD patterns are similar to Figure 2 The peak intensity ratio of I(003) / I(104) and the c / a ratio of the lattice parameters of the ternary cathode material were determined, and the specific results are shown in Table 1.
[0108] (2) Electrochemical properties of cathode materials
[0109] Lithium batteries were assembled according to the method described in Example 1 and the electrochemical performance was tested.
[0110] The electrochemical performance at a rate of 0.1C was measured, and the specific results are shown in Table 2.
[0111] [Example 7]
[0112] (1) Preparation and evaluation of ternary cathode materials
[0113] Take 10g of high nickel ternary cathode material precursor Ni 0.83 Co 0.05 Al 0.12 (OH)2, add 5g LiOH·H2O particles and mix and grind thoroughly;
[0114] The obtained homogeneous powder was subjected to high temperature treatment in a tube furnace and calcined in an oxygen atmosphere. The specific process was as follows: the temperature was increased from 25°C to 500°C at a heating rate of 5°C / min, maintained for 7 hours, then increased to 900°C at a heating rate of 10°C / min, maintained for 4 hours, then cooled to 700°C at a cooling rate of 5°C / min, maintained for 12 hours, and then naturally cooled to below 100°C and taken out;
[0115] The powder obtained after high-temperature calcination was ball-milled for 2 hours to obtain the ternary positive electrode material.
[0116] SEM image of the ternary cathode material obtained in Example 7 Figure 1 Similarly, its primary particle size is 3.3-3.5 μm. XRD pattern is similar to Figure 2 The peak intensity ratio of I(003) / I(104) and the c / a ratio of the lattice parameters of the ternary cathode material were determined, and the specific results are shown in Table 1.
[0117] (2) Electrochemical properties of cathode materials
[0118] Lithium batteries were assembled according to the method described in Example 1 and the electrochemical performance was tested.
[0119] The electrochemical performance at a rate of 0.1C was measured, and the specific results are shown in Table 2.
[0120] [Comparative Example 1]
[0121] (1) Preparation and evaluation of ternary cathode materials
[0122] Take 10g of high nickel ternary cathode material precursor Ni 0.83 Co 0.05 Mn 0.12 (OH)2, add 5g LiOH·H2O particles and mix and grind thoroughly.
[0123] The obtained homogeneous powder was subjected to high temperature treatment in a tube furnace and calcined in an oxygen atmosphere at a heating rate of 5°C / min from 25°C to 550°C, maintained for 7h, and then heated to 900°C at a heating rate of 10°C / min, maintained for 12h, and naturally cooled to below 100°C before being taken out;
[0124] The powder obtained after high-temperature calcination was ball-milled for 2 hours to obtain the ternary positive electrode material.
[0125] SEM image of the ternary positive electrode material obtained in Comparative Example 1 Figure 1 Similarly, the primary particle size is 3.5-3.8 μm. XRD patterns are similar to Figure 2 The peak intensity ratio of I(003) / I(104) and the c / a ratio of the lattice parameters of the ternary cathode material were determined, and the specific results are shown in Table 1.
[0126] (2) Electrochemical properties of cathode materials
[0127] Lithium batteries were assembled according to the method described in Example 1 and the electrochemical performance was tested.
[0128] The electrochemical performance at a rate of 0.1C was measured, and the specific results are shown in Table 2.
[0129] [Comparative Example 2]
[0130] (1) Preparation and evaluation of ternary cathode materials
[0131] Take 10g of high nickel ternary cathode material precursor Ni 0.83 Co 0.12 Mn 0.05 (OH)2, add 5g LiOH·H2O particles and mix and grind thoroughly;
[0132] The obtained homogeneous powder was subjected to high temperature treatment in a tube furnace and calcined in an oxygen atmosphere at a heating rate of 5°C / min from 25°C to 550°C, maintained for 7h, and then heated to 930°C at a heating rate of 8°C / min, maintained for 12h, and naturally cooled to below 100°C before being taken out;
[0133] The powder obtained after high-temperature calcination was ball-milled for 2 hours to obtain the ternary positive electrode material.
[0134] The SEM image of the ternary positive electrode material obtained in Comparative Example 2 is Figure 1 Similarly, the primary particle size is 4.0-4.5 μm. XRD patterns are similar to Figure 2 The peak intensity ratio of I(003) / I(104) and the c / a ratio of the lattice parameters of the ternary cathode material were determined, and the specific results are shown in Table 1.
[0135] (2) Electrochemical properties of cathode materials
[0136] Lithium batteries were assembled according to the method described in Example 1 and the electrochemical performance was tested.
[0137] The electrochemical performance at a rate of 0.1C was measured, and the specific results are shown in Table 2.
[0138] [Comparative Example 3]
[0139] (1) Preparation and evaluation of ternary cathode materials
[0140] Take 10g of high nickel ternary cathode material precursor Ni 0.83 Co 0.05 Mn 0.12 (OH)2, add 5g LiOH·H2O particles and mix and grind thoroughly;
[0141] The obtained homogeneous powder was subjected to high temperature treatment in a tube furnace and calcined in an oxygen atmosphere. The specific process was as follows: the temperature was increased from 25°C to 500°C at a heating rate of 5°C / min, maintained for 7h, then increased to 700°C at a heating rate of 10°C / min, maintained for 4h, then increased to 900°C at a heating rate of 10°C / min, maintained for 12h, and then naturally cooled to below 100°C and taken out;
[0142] The powder obtained after high-temperature calcination was ball-milled for 2 hours to obtain the ternary positive electrode material.
[0143] SEM image of the ternary positive electrode material obtained in Comparative Example 3 Figure 1 Similarly, the primary particle size is 3.7-3.9 μm. XRD patterns are similar to Figure 2 The peak intensity ratio of I(003) / I(104) and the c / a ratio of the lattice parameters of the ternary cathode material were determined, and the specific results are shown in Table 1.
[0144] (2) Electrochemical properties of cathode materials
[0145] Lithium batteries were assembled according to the method described in Example 1 and the electrochemical performance was tested.
[0146] The electrochemical performance at a rate of 0.1C was measured, and the specific results are shown in Table 2.
[0147] [Comparative Example 4]
[0148] (1) Preparation and evaluation of ternary cathode materials
[0149] Take 10g of high nickel ternary cathode material precursor Ni 0.83 Co 0.05 Mn 0.12 (OH)2, add 5g LiOH·H2O particles and mix and grind thoroughly;
[0150] The obtained homogeneous powder was subjected to high temperature treatment in a tube furnace and calcined in an oxygen atmosphere. The specific process was as follows: the temperature was increased from 25°C to 700°C at a heating rate of 5°C / min, maintained for 7 hours, then increased to 900°C at a heating rate of 10°C / min, maintained for 4 hours, then cooled to 500°C at a cooling rate of 10°C / min, maintained for 12 hours, and then naturally cooled to below 100°C and taken out;
[0151] The powder obtained after high-temperature calcination was ball-milled for 2 hours to obtain the ternary positive electrode material.
[0152] The SEM image of the ternary positive electrode material obtained in Comparative Example 4 is Figure 1 Similarly, the primary particle size is 4.3-4.6 μm. XRD patterns are similar to Figure 2 The peak intensity ratio of I(003) / I(104) and the c / a ratio of the lattice parameters of the ternary cathode material were determined, and the specific results are shown in Table 1.
[0153] (2) Electrochemical properties of cathode materials
[0154] Lithium batteries were assembled according to the method described in Example 1 and the electrochemical performance was tested.
[0155] The electrochemical performance at a rate of 0.1C was measured, and the specific results are shown in Table 2.
[0156] Table 1 Physicochemical properties of the single crystal ternary cathode materials obtained in each example
[0157] sample Ternary cathode materials I(003) / I(104) c / a Lithium nickel mixing degree Example 1 <![CDATA[LiNi 0.83 What 0.05 Mn 0.12 O2]]> 2.139 4.9387 1.722% Example 2 <![CDATA[LiNi 0.83 What 0.12 Mn 0.05 O2]]> 2.045 4.9374 2.437% Example 3 <![CDATA[LiNi 0.83 What 0.05 Mn 0.12 O2]]> 1.936 4.9380 1.938% Example 4 <![CDATA[LiNi 0.83 What 0.12 Mn 0.05 O2]]> 2.064 4.9367 3.184% Example 5 <![CDATA[LiNi 0.83 What 0.05 Mn 0.12 O2]]> 2.125 4.9394 1.380% Example 6 <![CDATA[LiNi 0.83 What 0.05 Mn 0.12 O2]]> 2.129 4.9389 1.829% Example 7 <![CDATA[LiNi 0.83 Yes 0.05 Al 0.12 O2]]> 1.925 4.9374 2.764% Comparative Example 1 <![CDATA[LiNi 0.83 What 0.05 Mn 0.12 O2]]> 1.701 4.9359 6.722% Comparative Example 2 <![CDATA[LiNi 0.83 What 0.12 Mn 0.05 O2]]> 1.082 4.9266 14.61%
[0158]
[0159] Table 2 Electrochemical performance test results of the single crystal ternary cathode materials obtained in each example
[0160]
[0161] The above describes the specific implementation of the present invention in detail, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the various technical features being combined in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A single crystal ternary cathode material, whose chemical formula is Li x Ni y Co z M a O b , wherein M is at least one of Mn and Al; 0.8≤x<1.2, 0.6≤y≤0.95, 0<z≤0.2, 0<a≤0.2, and the proportion of oxygen element conforms to the principle of electrical neutrality according to the valence state and content of different elements; in the positive electrode material, the lithium-nickel mixing degree s is less than 4%, preferably less than 2%.
2. The single crystal ternary cathode material according to claim 1, characterized in that: In the single crystal ternary positive electrode material, 0.9≤x<1.1, 0.8≤y≤0.95, 0<z≤0.15, 0<a≤0.15; preferably, 0.9≤x<1.1, 0.8≤y≤0.95, 0<z≤0.05, 0<a≤0.
15.
3. The single crystal ternary cathode material according to claim 1 or 2, characterized in that: In the single crystal ternary positive electrode material, the size of the primary particles is 2.0-5.0 μm, preferably 3.0-5.0 μm.
4. The single crystal ternary cathode material according to claim 1, characterized in that: In the XRD spectrum of the single crystal ternary positive electrode material, the diffraction peak intensities I(003) and I(104) of the crystal plane (003) and the crystal plane (104) satisfy the following relationship: I(003) / I(104) is greater than 1.800, preferably greater than 1.900, and further preferably greater than 2.
000.
5. The single crystal ternary cathode material according to claim 1, characterized in that: In the single crystal ternary positive electrode material, the c / a ratio in the lattice parameter is greater than 4.9350, preferably greater than 4.9365, and further preferably greater than 4.9380.
6. A process for preparing a single crystal ternary cathode material, comprising the following steps: The ternary cathode material precursor is mixed with a lithium source, calcined, and crushed to obtain the single crystal ternary cathode material.
7. The preparation process according to claim 6, characterized in that: The calcination adopts three-stage programmed temperature control calcination, wherein the temperature T1 of the first stage calcination is 400-600°C, the calcination time t1 is 4-7 hours, the temperature T2 of the second stage calcination is 800-1100°C, the calcination time t2 is 0.1-6 hours, and the temperature T3 of the third stage calcination is 600-900°C, and the calcination time t3 is 6-18 hours.
8. The preparation process according to claim 6, characterized in that: The temperature T1 of the first stage calcination is 450-550°C, the time t1 is 5-7 hours, and the heating rate is 2-8°C / min; the temperature T2 of the second stage calcination is 850-1000°C, the time t2 is 0.5-4 hours, and the heating rate is 2-10°C / min; the temperature T3 of the third stage calcination is 700-800°C, the time t3 is 9-15 hours, and the cooling rate is 2-10°C / min.
9. The preparation process according to claim 7 or 8, characterized in that: t2 is smaller than t1 and t3, and T2 is larger than T1 and T3; preferably, the calcination temperature and time follow the rule of t3>t1>t2, and T2>T3>T1.
10. The preparation process according to claim 6, characterized in that: The lithium source is one or more of anhydrous lithium hydroxide, lithium hydroxide monohydrate, lithium carbonate, lithium phosphate, and lithium oxalate, preferably one or more of anhydrous lithium hydroxide and lithium hydroxide monohydrate.
11. The preparation process according to claim 6, characterized in that: The ternary cathode material precursor is a hydroxide precursor containing nickel-cobalt-manganese, nickel-cobalt-aluminum or nickel-cobalt-manganese-aluminum, and its chemical formula is Ni y Co z M a (OH)2, wherein M is at least one of Mn and Al; 0.6≤y≤0.95, 0<z≤0.2, 0<a≤0.2, and y+z+a=1; preferably, 0.8≤y≤0.95, 0<z≤0.15, 0<a≤0.15, and y+z+a=1; further preferably, 0.8≤y≤0.95, 0<z≤0.05, 0<a≤0.15, and y+z+a=1.
12. The preparation process according to claim 6, characterized in that: The molar ratio of the lithium source to the ternary cathode material precursor is 1:1 to 1.3:1, preferably 1.05:1 to 1.2:1; And / or, the crushing method is air flow crushing or ball mill crushing, and the crushing time is 2-10 hours.
13. The preparation process according to claim 6, characterized in that: The chemical formula of the single crystal ternary cathode material is Li x Ni y Co z M a O b , wherein M is at least one of Mn and Al; 0.8≤x<1.2, 0.6≤y≤0.95, 0<z≤0.2, 0<a≤0.2, and the proportion of oxygen element conforms to the principle of electrical neutrality according to the valence state and content of different elements.
14. A single crystal ternary positive electrode material prepared by the process described in any one of claims 6 to 14.
15. Use of the single crystal ternary cathode material according to any one of claims 1 to 5 or the single crystal ternary cathode material according to claim 14 in a lithium ion battery.
Citation Information
Patent Citations
Preparation method of high-nickel ternary material
CN108346797A
Single-crystal ternary positive electrode material, preparation method thereof and lithium ion battery
CN112018372A
High-nickel single-crystal nickel-cobalt-aluminum ternary positive electrode material and preparation method thereof
CN113422046A
Spherical-like single crystal positive electrode material and preparation method thereof
CN114481322A
Method for preparing high-capacity single-crystal ternary positive electrode material by infiltration dispersion method
CN114703545A